Semaphorin 3A mitigates lipopolysaccharide-induced chondrocyte inflammation, apoptosis and extracellular matrix degradation by binding to Neuropilin-1. Issue 2 (20th December 2021) - Zhang, Huiyu; Lu, Yue; Wu, BingBing; Xia, Fei
ABSTRACT: Semaphorin 3A (SEMA3A) and its receptor neuropilin-1 (NRP-1) are expressed low in chondrocytes under stress, and overexpressing SEMA3A reduces pro-inflammatory cytokine release. This study was aimed at exploring whether SEMA3A participates in lipopolysaccharide (LPS)-induced chondrocyte inflammation, apoptosis and extracellular matrix (ECM) degradation. SEMA3A and NRP-1 expression in LPS-induced ATDC5 cells was determined with RT-qPCR and western blotting. Following stimulation with LPS in the absence or presence of SEMA3A overexpression, the viability of ATDC5 cells was observed through CCK-8 assay. RT-qPCR and western blot were performed to detect the expression of pro-inflammatory cytokines. ATDC5 cell apoptosis was observed through TUNEL, and apoptosis-related proteins were assayed. Expression of ECM-related proteins was measured by RT-qPCR and western blotting. Additionally, the binding of SEMA3A to NRP-1 was verified by co-immunoprecipitation. After interference with NRP-1, cell viability, inflammation and ECM degradation were examined in LPS-induced ATDC5 cells with SEMA3A overexpression. Results revealed that SEMA3A expression in ATDC5 cells decreased following stimulation with LPS. Overexpressing SEMA3A improved cell viability and reduced the inflammatory injury of LPS-stimulated ATDC5 cells. Moreover, SEMA3A overexpression alleviated LPS-induced apoptosis and ECM degradation of ATDC5 chondrocytes. SEMA3A and NRP-1 bound to each other in ATDC5 cells. NRP-1 interference crippled the ameliorative effect of SEMA3A overexpression on LPS-induced chondrocyte inflammation, apoptosis and ECM degradation. To conclude, SEMA3A binds to NRP-1, mitigating LPS-induced chondrocyte inflammation, apoptosis and ECM degradation. This study elucidated the role of SEMA3A in osteoarthritis and illustrated its action mechanism involving NRP-1.